Graphene Fibers with Predetermined Deformation as Moisture‐Triggered Actuators and Robots1. Issue 40 (14th August 2013) - Cheng, Huhu; Liu, Jia; Zhao, Yang; Hu, Chuangang; Zhang, Zhipan; Chen, Nan; Jiang, Lan; Qu, Liangti
<x xml:space="preserve">Abstract</x> Enough to make your hair curl! Moisture‐responsive graphene (G) fibers can be prepared by the positioned laser reduction of graphene oxide (GO) counterparts. When exposed to moisture, the asymmetric G/GO fibers display complex, well‐controlled motion/deformation in a predetermined manner. These fibers can function not only as a single‐fiber walking robot under humidity alternation but also as a new platform for woven devices and smart textiles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>